2014
DOI: 10.1371/journal.pone.0084511
|View full text |Cite
|
Sign up to set email alerts
|

HPTN 071 (PopART): A Cluster-Randomized Trial of the Population Impact of an HIV Combination Prevention Intervention Including Universal Testing and Treatment: Mathematical Model

Abstract: BackgroundThe HPTN 052 trial confirmed that antiretroviral therapy (ART) can nearly eliminate HIV transmission from successfully treated HIV-infected individuals within couples. Here, we present the mathematical modeling used to inform the design and monitoring of a new trial aiming to test whether widespread provision of ART is feasible and can substantially reduce population-level HIV incidence.Methods and FindingsThe HPTN 071 (PopART) trial is a three-arm cluster-randomized trial of 21 large population clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 45 publications
2
85
0
2
Order By: Relevance
“…This finding has generated interest in understanding the population-level impact of HIV treatment on reducing the rate of new HIV infections in generalized epidemic settings (4). Research, including mathematical modeling (5-10), implementation research (11), and major randomized controlled trials (12)(13)(14), are focused on how ART provision might be expanded strategically to maximize its public health benefits (15, 16).One concern is that if a large fraction of HIV transmission occurs shortly after a person becomes infected, before the person can be diagnosed and initiated on ART, this will limit the potential impact of HIV treatment on reducing HIV incidence (9,17,18). Data suggest that persons are more infectious during a short period of "early infection" after becoming infected with HIV (19-22), although there is debate about the extent, duration, and determinants of elevated infectiousness (18, 23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has generated interest in understanding the population-level impact of HIV treatment on reducing the rate of new HIV infections in generalized epidemic settings (4). Research, including mathematical modeling (5-10), implementation research (11), and major randomized controlled trials (12)(13)(14), are focused on how ART provision might be expanded strategically to maximize its public health benefits (15, 16).One concern is that if a large fraction of HIV transmission occurs shortly after a person becomes infected, before the person can be diagnosed and initiated on ART, this will limit the potential impact of HIV treatment on reducing HIV incidence (9,17,18). Data suggest that persons are more infectious during a short period of "early infection" after becoming infected with HIV (19-22), although there is debate about the extent, duration, and determinants of elevated infectiousness (18, 23).…”
mentioning
confidence: 99%
“…This finding has generated interest in understanding the population-level impact of HIV treatment on reducing the rate of new HIV infections in generalized epidemic settings (4). Research, including mathematical modeling (5-10), implementation research (11), and major randomized controlled trials (12)(13)(14), are focused on how ART provision might be expanded strategically to maximize its public health benefits (15, 16).…”
mentioning
confidence: 99%
“…Is this sort of behavioural change possible? Variations in concurrency within West Africa and across SSA suggest that alternative behavioural norms can become established, 28 but even small changes to sexual behaviour over a sustained time may be challenging, especially compared with a one-time circumcision surgery. 29 Assuming no behavioural change, our study suggested that targeting MMC should depend on epidemiological context.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the HPTN 071/PopART model estimates a 60 % reduction in HIV incidence when compared to current standard care. This impact is importantly dependent on high coverage of ART aligned to the UNAIDS Fast-Track Targets [24,25].…”
Section: The Expanding Role Of Combination Hiv Prevention Packagesmentioning
confidence: 99%